Sprint cycling rate of torque development associates with strength measurement in trained cyclists - Connolly, S.; Peeling, P.; Binnie, M. J.; Goods, P. S. R.; Latella, C.; Taylor, J. L.; Blazevich, A. J.; Timmerman, W. P.; Abbiss, C. R. (European Journal of Applied Physiology, 2023)
Purpose A cyclist`s rate of force/torque development (RFD/RTD) and peak force/torque can be measured during single-joint or whole-body isometric tests, or during cycling. However, there is limited understanding of the relationship between these measures, and of the mechanisms that contribute to each measure. Therefore, we examined the: (i) relationship between quadriceps central and peripheral neuromuscular function with RFD/RTD in isometric knee extension, isometric mid-thigh pull (IMTP), and sprint cycling; and (ii) relationship among RFD/RTD and peak force/torque between protocols.